The effects of social defeat stress on hippocampal glial cells and interleukin-6 in adolescence and adulthood. Issue 18 (1st November 2022) - Xu, Yingjuan; Zhang, Jiling; Fang, Zeman; Zhang, Handi
Abstract : Adolescent social stress has been associated with the vulnerability to developing psychopathological disorders in adulthood that are accompanied by brain inflammatory processes. The purpose of this study is to investigate the dynamic changes of the hippocampal neuroinflammatory mediators, including microglia, astrocyte, and interleukin-6 (IL-6) levels in mice experiencing social defeat stress during adolescence. Adolescent mice were divided into the control group and stress group. Mice in the stress group were exposed to chronic intermittent social defeat for a total of 12 days, and control mice were reared in normal conditions. The hippocampal microglia, astrocyte, and IL-6 levels were measured 24 h and 3 weeks after the end of stress exposure. Microglia activation characterized by increased ionized calcium-binding adapter molecule 1 positive cell numbers or staining area in the CA1 and CA3 regions of the hippocampus were observed 24 h after the end of stress, which did not last into the adulthood. No short-term or long-term alterations of the number of hippocampal CA1 and CA3 glia fibrillary acidic protein astrocytes were found in mice experiencing adolescent social defeat, whereas IL-6 levels were only increased 3 weeks after the end of stress. These data suggested that exposure to chronic social defeat stress led to short-term and long-term neuroinflammatory changes in the hippocampus.